(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Most parents of hospitalized children suffer from psychological problems such as anxiety and stress. The use of coping mechanisms plays an important role in maternal adjustment of these parents. Spiritual self-care is one of the aspects of self-care, which plays an important role in stress adaptation. Therefore, this study was conducted to determine the effect of spiritual self-care training on the anxiety of mothers of premature infants admitted to NICUs.Methods: This classic experimental study was conducted on 64 mothers of neonates admitted to NICU. The selected mothers were divided into two groups of intervention (n=32) and control (n=32) by simple random method. The data were collected by Spielberger State and Trait Anxiety Inventory (STAI). Routine nursing care was provided to samples in the control group and those in the intervention group, received 6 training sessions (20-30 minutes) based on the selected educational content. Data were analyzed by SPSS-20 statistical software using descriptive statistics (table, mean, standard deviation) and inferential statistics (paired t-test, independent t-test, ANCOVA) at a significant level of 0.05.Conclusion: Before the intervention, the anxiety level of samples in the intervention group was 117.88 + 13.6 and in the control group was 119.88 + 17.85. The independent t-test did not show a significant difference between the two groups in that regard before the intervention (P = 0.54). ANCOVA test showed a significant difference between the two groups of intervention and control by removing the effect of pre-test (P <0.01 and Eta = 0.12), so that 12% of the changes in anxiety level was related to the spiritual self-care training of mothers.Discussion & Conclusion: Considering the effectiveness of spiritual self-care training on reducing the anxiety of mothers of hospitalized neonates, we can expect nurses as important members of multidisciplinary team to play an important role in identifying patients' spiritual needs and meeting them. Because spiritual self-care is considered as a low-cost, effective and low-risk care method.